Finest frugt - om ‘den Vartou Kjællingepræst’: En guide til Grundtvig-Studier 1948-2008, II - Jørgensen, Aage (Grundtvig-Studier, 2010)
Finest frugt - om ‘den Vartou Kjællingepræst’: En guide til Grundtvig- Studier 1948-2008, II [Fruit of the finest - concerning (the Vartov Old Biddies ’past or A guide to Grundtvig-Studier 1948-2008, II] By Aage Jørgensen As early as 1948, the Grundtvig Society of 8 September 1947 launched an annual journal, Grundtvig-Studier. Since then, the journal has published a significant part of the subsequent research on Grundtvig, including important debate on the many Grundtvig dissertations that have appeared since World War II. This article is the second part of an anniversary retrospect introduced in Grundtvig-Studier 2009 which reviews the content of the volumes of Grundtvig-Studier hitherto issued. It deals with contributions to the journal on Grundtvig’s educational deliberations and their significance for Danish schools, especially the folkhighschools, together with the overall subsequent reception of his pedagogical thinking both within Denmark and in the wider world.